(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2020)
This paper explores the various ideals of beauty which globalization has created for women at the international, national and local level. It also highlights the various facets of beauty pageants which feed into these ideal types and notions. Furthermore, this paper looks at the claim that beauty pageants make, of being inclusive of diversity. Despite having women from different cultures, race and countries participate and even win the Miss World pageant, there are still a lot of categories which have been left out and the pageants are not completely inclusive. We have never seen a Fat Miss World or a Short Miss World. This paper calls attention to how these aesthetics are very usual but they have been completely excluded from the wider scope of the contest which idealizes unrealistic feminine standards of beauty.